Assessment of a Novel Vitamin D3 Formulation with Nanostructured Lipid Carriers for Transdermal Delivery - Junqueira, Laura; Polonini, Hudson; Ramos, Cristiano; Ferreira, Anderson O.; Raposo, Nádia; Brandão, Marcos (Current Drug Delivery, 2022)
Objective: Develop and assess a transdermal emulsion loaded with nanostructured lipid carriers for vitamin D3 supplementation. Methods: Vitamin D3 loaded nanostructured lipid carriers, produced via high shear homogenization and ultrasonication, were assessed for their particle size, distribution, morphology, zeta potential, entrapment efficiency, and cytotoxicity. They were incorporated into a transdermal vehicle, and the stability and ex vivo permeation were evaluated. Results: Spherical nanoparticles were developed with a particle size of 192.5 nm, a polydispersity index of 0.13, a zeta potential of -29.0 mV, and an entrapment efficiency of 99.75%. They were stable (particle size and distribution) for 15 days when stored in a refrigerator, and for 30 days at room temperature and 32°C. The nanoparticles decreased the drug cytotoxicity against fibroblasts, as shown by IC50 (nanoparticle: 32.48 μg mL−1; vitamin D3: 16.73 μg mL−1). The emulsion loaded with nanoparticles minimized the degradation of vitamin D3 when compared with the nanoparticle dispersion. Additionally, the emulsion provided the skin permeation of vitamin D3 following the recommended daily allowance. Conclusion: To the best of our knowledge, this is the first study to use nanostructured lipid carriers for transdermal delivery of vitamin D. The developed formulation is a promising strategy to overcome the vitamin D3 variable oral bioavailability. It also represents a comfortable route of administration; thus it could be beneficial for patients and clinicians. However, further studies are needed to allow the permeation of larger amounts of vitamin D3, and the combination of these nanoparticles with microneedles would be interesting.
Keywords: ex vivo permeation